Experimental and Modeling Study for the Solar-Driven CO2 Electrochemical Reduction to CO - Matteo Agliuzza; Roberto Speranza; Andrea Lamberti; Candido Fabrizio Pirri; Adriano Sacco (Applied Sciences)
With the rising levels of atmospheric CO2, electrochemistry shows great promise in decarbonizing industrial processes by converting CO2 into valuable products through scalable and sustainable technologies. In this framework, the present study investigates the solar-driven CO2 reduction toward carbon monoxide, achieved by the integration between the electrochemical reactor and dye-sensitized solar cells (DSSCs), both in experimental and modeling perspectives. COMSOL® Multiphysics 6.3 was used to develop a detailed finite element method model of the electrochemical cell integrated with a photovoltaic module, validated with the experimental results that demonstrated a strong correlation. A 2D model was designed, incorporating cathode and anode regions divided by an ion-exchange membrane. The model includes platinum foil and silver nanoparticles as catalysts for the oxygen evolution reaction and CO2 reduction reaction, respectively. Integration with the fundamental equations of the DSSCs was simulated to analyze the solar-driven CO2 reduction behavior under solar irradiance variations, offering a valuable tool for optimizing operating conditions and predicting the device performance under different environmental conditions. The integrated device successfully produces CO with a faradaic efficiency of 73.85% at a current density of J = 3.35 mA/cm2 under 1 sun illumination, with the result validated and reproduced by the mathematical model. Under reduced illumination conditions of 0.8 and 0.6 suns, faradaic efficiencies of 68.5% and 64.1% were achieved, respectively.